Assigning Gender Role in Chitra Banerjee Divakaruni’s Sister of My Heart - Bhusal, Damodar (Academia Research Journal, 2022)
Chitra Banerjee Divakaruni through her novel Sister of My Heart unveils the position of women and their roles assigned in Indian patriarchal society and their effort to overthrow the biased attitude of male. As its theoretical tool it utilizes western version of liberal feminism and gender theory as stated by David Glover and Cora Kaplan. In doing so it aims at examining the reality of patriarchal ideology which considers women as second class citizen and maternal vessels. It reveals the pathetic condition of the protagonist, Anju and Sudha. They have not got the role of independent agents in the society but treated as play things. They are taught to be submissive from the very beginning of their life. The demarcation line has been drawn in the name of Bidhata Purush who also does not come to write their fortune. As a result, directly or indirectly they are engaged in their subservient lives. It is patriarchal ideology which makes them feminine and masculine, which assigns different roles, rights and responsibilities in order to make subservient. This paper concludes that the writer’s, Chitra Banerjee Divakaruni’s work exposes the male domination upon women in the Indian society.